2018
DOI: 10.1016/j.aquatox.2018.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular partitioning of metals and metalloids (As, Cd, Cu, Se and Zn) in liver and gonads of wild white suckers (Catostomus commersonii) collected downstream from a mining operation

Abstract: In the present study, we examined the subcellular distribution of metals and metalloids (As, Cd, Cu, Se and Zn) in the liver and gonads of wild white suckers (Catostomus commersonii) collected downstream from a metal mining operation (exposure area) and in a reference area. Metal partitioning among potentially metal-sensitive fractions (heat-denatured proteins (HDP), mitochondria and microsomes) and potentially biologically detoxified fractions (heat-stable proteins (HSP) and metal-rich granules) within cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 39 publications
6
24
0
Order By: Relevance
“…Comparisons between total [Cu] and [Cu] HSP indicate that the contribution of the HSP fraction to the total metal burden was above 60%; only for the testes was this contribution lower (≈20%). Similar relative contributions were previously reported in Urien et al [10].…”
Section: Copper (Cu)supporting
confidence: 91%
See 4 more Smart Citations
“…Comparisons between total [Cu] and [Cu] HSP indicate that the contribution of the HSP fraction to the total metal burden was above 60%; only for the testes was this contribution lower (≈20%). Similar relative contributions were previously reported in Urien et al [10].…”
Section: Copper (Cu)supporting
confidence: 91%
“…In a study on juvenile yellow perch (Perca flavescens) collected along an environmental contamination gradient, Giguère et al [9] observed that Cd and Cu present in fish livers were mainly associated with the HSP fraction, suggesting a detoxification response by the binding of these two metals to MT and/or MTLP. In our recent work, assessing subcellular metal and metalloid partitioning in the liver and gonads of field-collected white suckers (WS) from a reference lake and a contaminated lake, similar observations were reported for Cd and Cu; more than 60% of the total Cd and Cu burdens were associated with the HSP fraction [10]. In the same study, As was also found to be associated with the HSP fraction (close to 50%), whereas the Se burden was associated with both the HSP and HDP fractions, the contribution of the HSP fraction to the total hepatic Se burden being more important in exposed, as compared to reference, fish, suggesting the possible induction of a detoxification response in the fish.…”
Section: Introductionsupporting
confidence: 60%
See 3 more Smart Citations